Office Courtesy: Diferensiasi pada Komunikasi Organisasi - Yunus, Ulani (Humaniora, 2012)
Office etiquette or office courtesy is a procedure in a person with association or persons outside the organization. Etiquette teaches us to maintain good relations with the person / party. Etiquette becomes an inherent part of an organization because etiquette is not just a tool to assess an appropriate or inappropriate actions of members of the organization, but also the adhesive in the activities of a business transaction; that office image courtesy instrumental in building the organization. Through the courtesy of its contextual office applied through: adjustments to the organizational culture, attitudes toward seniors, standardization attitude towards the stakeholders. Thus, a typical office courtesy can be a differentiation of an organization.